Prispevek k filozofiji knjižničarstva in informacijske znanosti - Šercar, Tvrtko (Organizacija znanja, 2007)
This article represents a stimulus for debate and the resolving of key issues in several co-related fields: the divide between information philosophy and those philosophies and theories that are unjustifiably verlooked with regards to their relevance to librarianship and information science; knowledge and wisdom as categories of information science; professional responsibility for the philosophy of librarianship and information science; the connection between computer science and other sciences as a new scientific paradigm. Contextual (meta)analysis of selected relevant sources was used along with thephilosophical method of cognition by notions. Domain analysis was used in the case of the classification scheme of information science cognition. With regards to the chosen issues and purposes it was found that the philosophy of librarianship and information science builds the foundation of theoretical andpractical work in the professional environment of librarians and informatologists. The pluralistic rationalism of Karl Popper proved very useful to the philosophy of librarianship and information science. The 'data-information-knowledge-wisdom' model belongs to the domain of informationscience and/or the management and organisation of knowledge as a subdiscipline. For the philosophical discourse in librarianship and information sciences from this field, oriented towards theory and research aremost demanded, followed by professional philosophers as "outsiders". After introducing the "computer" paradigm to modern sciences, there is a pssibility for the philosophy of information science to become part of the philosophy of mathematics and sciences, where it had belonged prior to the "emancipation" ofsocial sciences, and where it could develop even further.
Keywords: bibliotekarstvo; filozofija; informacije; informatika; information science; knowledge; kritični racionalizem; library science; modrost; philosophy; podatki; razvojna epistemologija; science; vedoslovje; znanje; znanost